1990
DOI: 10.1017/s0003356100005535
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protein intake on energy and nitrogen balance and chemical composition of gain in growing boars of high genetic potential

Abstract: 1990). Effect of protein intake on energy and nitrogen balance and chemical composition of gain in growing boars of high genetic potential. ABSTRACT The effects of dietary protein (151 to 282 g crude protein per kg dry matter (DM)) and lysine (8-5 to 16-4 g/kg DM) on the carcass composition and energy metabolism of entire male pigs, given food close to appetite, was studied from 33 to 88 kg. Four replicates (three Landrace and one Duroc) of four littermates were used. Energy and nitrogen (N) balances were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

1992
1992
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 9 publications
1
14
0
2
Order By: Relevance
“…However there is still controversy as to whether the rate of protein deposition can be considered to be a constant over an extended weight range. For boars from a strain with high genetic potential for lean growth Rao and McCracken (1990) suggested a plateau for protein accretion between 35 and 80 kg live weight. Whittemore et al (1988) considered that to conclude protein deposition was a plateau and was often an artifact of a restricted weight range and serial slaughter design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However there is still controversy as to whether the rate of protein deposition can be considered to be a constant over an extended weight range. For boars from a strain with high genetic potential for lean growth Rao and McCracken (1990) suggested a plateau for protein accretion between 35 and 80 kg live weight. Whittemore et al (1988) considered that to conclude protein deposition was a plateau and was often an artifact of a restricted weight range and serial slaughter design.…”
Section: Discussionmentioning
confidence: 99%
“…Whittemore et al (1988) reviewed a number of studies in which the protein accretion rates were considered to approach the maximum achievable for that genotype and found that protein accretion rates ranged from 0090 to 0-175 kg/day. Rao and McCracken (1990) reported rates up to 0-200 kg/day for entire males from a strain of high genetic potential for lean growth. In most of these studies the higher estimates for protein deposition were generally for entire males, which in comparative studies have been reported to have rates which are 112 to 1-33 times those found in castrated males and gilts (Whittemore et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the lysine:calorie ratio in diets fed to growing pigs improved ADG and ADFI (linear, P < .01 and .07, respectively). Many trials have shown increased growth performance when growing pigs were fed diets with increased lysine concentration (Yen et al, 1986;Rao and McCracken, 1990;Hansen and Lewis, 1993). Several other trials have examined the effect of lysine concentration on growth performance when dietary energy levels were maintained, in essence examining the effect of varying lysine:calorie ratios.…”
Section: Experiments 2 No Interactive Effects Of Energy Densitymentioning
confidence: 99%
“…To explain the variation in response to increasing energy in swine diets, several studies have examined the relationship between energy and protein content of the diet and have shown positive correlations. Increasing the lysine:energy ratio in growing pig diets improved ADG and G:F (Batterham et al, 1985;Rao and McCracken, 1990;Chiba et al, 1991). Van Lunen and Cole (1996) observed that increasing the lysine:calorie ratio decreased backfat depth in high-lean-growth pigs without affecting growth rate.…”
Section: Introductionmentioning
confidence: 97%
“…Apesar de estarem em acordo com os dados obtidos por Pimenta et al (1995) e Gomes (1998), os valores de TCM e CAM, neste experimento, foram superiores, em valor absoluto, aos encontrados por esses autores. Segundo Rao & McCracken (1990), Friesen et al (1994) e Pimenta et al (1995), o potencial genético para ganho de músculo é um dos principais fatores que influem na taxa de crescimento e na conversão alimentar. Na Tabela 3, são apresentados os resultados das taxas de deposição de proteína (TDP) e gordura (TDG) na carcaça das leitoas.…”
Section: Nível De Lisina (%)unclassified